COOPERATION OF UKRAINE WITH INTERNATIONAL ORGANIZATIONS IN FORMATION OF EUROPEAN SECURITY IN THE CONDITIONS OF "HYBRID WAR" ON THE EASTERN UKRAINE - Дрогомирецька, В. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the problem of the modern "hybrid war" on the example of an armed conflict in the East of Ukraine. The peculiarities of the phenomenon of hybrid war are revealed and the meaning of the term "hybrid war" is determined. The cooperation of Ukraine during the armed conflict in the Donetsk and Luhansk oblasts with international organizations such as the UN and the OSCE has been explored. Their essence and the concrete influence of their activity on resolving the conflict in the Donbass are revealed. Essence of international safety is grounded, as a system of international relations, which is based on the observance of norms of international law. A concept «international safety is considered». Statistics of United Nations are investigational in relation to events on Donbass, namely amount of victims on Donbass from the beginning of military operations.